1454 Early markers of cardiovascular disease are associated with occupational exposure to polycyclic aromatic hydrocarbons. (24th April 2018) - Alhamdow, Ayman; Lindh, Christian; Albin, Maria; Gustavsson, Per; Tinnerberg, Håkan; Broberg, Karin
Abstract : Introduction: Occupational exposure to polycyclic aromatic hydrocarbons (PAH) from soot is common and has been associated with increased risk of cardiovascular disease (CVD); the association, however, has only been indicated, not established. Our aim was to investigate occupational exposure to PAH and early markers of CVD. Methods: A cross-sectional study of 151 chimney sweeps and 152 controls, all males, from Sweden was conducted between 2011–2015. Participants answered a questionnaire and gave blood and urine samples. Urinary PAH metabolites were measured using LC-MS/MS: 1-hydroxypyrene (1-OH-PYR), 2-hydroxyphenanthrene (2-OH-PH), 3-hydroxybenzo[a]pyrene (3-OH-BaP), and 3-hydroxybenzo[a]anthracene (3-OH-BaA). Blood pressure (BP) and serum biomarkers were measured (C-reactive protein, homocysteine, gamma-glutamyltransferase, cholesterol, HDL, LDL, and triglycerides), to estimate the risk of CVD. Results: Chimney sweeps had up to 7-fold higher concentrations of PAH metabolites in urine than controls (p<0.001): median concentrations (adjusted for specific gravity) for 1-OH-PYR, 2-OH-PH, 3-OH-BaP, and 3-OH-BaA were 0.56 µg/L, 0.78 µg/L, 4.75 ng/L, and 6.28 ng/L, respectively. PAH metabolites correlated positively with the amount of soot sweeping as a percentage of total work (p<0.001). Chimney sweeps had increased homocysteine, cholesterol, and HDL ( β =3.4 µmol/L, 0.43 mmol/L, and 0.13 mmol/L, respectively, p≤0.003, adjusted for age, BMI, and smoking). 2-OH-PH, 3-OH-BaP, and 3-OH-BaA were positively associated with diastolic BP in chimney sweeps (p<0.044, adjusted for age, BMI, and smoking). Conclusions: Working with soot resulted in clear exposure to PAH, and in turn, an elevated risk for CVD. These findings indicate the need to raise awareness of protective measures that can decrease PAH exposure during work and in the general environment.